The Louise A. Boyd expedition to East Greenland, 1933 : Photogrammetrical survey of the Gregory Valley, east Greenland / O.M. Miller, surveyor in charge - Boyd, Louise Arner, 1887-1972 (A. Hoen & Co., 1933)
Relief shown by contours. Includes inset "reliability diagram." "Amer. Geogr. Soc. special publ. no. 18, Pl. I" -- upper right margin. Color 1:50,000